Pemanfaatan Wireless Fidelity (WIFI) Di Perguruan Tinggi Sebagai Fasilitas Kegiatan Akademik Mahasiswa : (Utilization of Wireless Fidelity (WIFI) in Higher Education as a Facility for Student Academic Activities) - Dinda Listya; Dini Fitria; Elva Triyana; Nur Asni (BIODIK, 2023)
This study aims to determine the use of Wifi for students at Samudra University College. This type of research uses descriptive research, the research approach used is a qualitative approach. The research instrument was distributing questionnaires (questionnaires) which were carried out in March-April 2022. The sample in this study was 200 students consisting of 5 (five) faculties at Samudra University. The results of this study indicate that out of 100% of students, only 86% have used the Wifi available at Samudra University College. Utilization of Wifi is widely used in supporting student academic activities in Higher Education. Key words: Wireless Fidelity (Wifi), questionnalire, alcaldemic Â  ABSTRAK Penelitialn ini bertujualn untuk mengetalhui pemalnfalaltaln Wifi balgi malhalsiswal di Pergurualn Tinggi Universitals Salmudral. Jenis penelitialn ini menggunalkaln penelitialn deskriptif, pendekaltaln penelitialn yalng digunalkaln yalitu pendekaltaln kuallitaltif. Instrument penelitialn ini yalitu penyebalraln kuesioner (alngket) yalng dilalksalnalkaln paldal bulaln Malret-Alpril 2022. Salmpel dallalm penelitialn ini sebalnyalk 200 malhalsiswal/I yalng terdiri dalri 5 (limal) falkultals di Universitals Salmudral. Halsil penelitialn ini mengindikalsikaln balhwa, dari 100%mahasiswa/I ternyata hanyal 86% saja yangl pernalh memanfaatkan Wifi yalng tersedial di Pergurualn Tinggi Universitals Salmudral. Pemanfaatan Wifi tersebut balnyalk digunakan dalam mendukung kegiatan akademik mahasiswa/I di Perguruan Tinggi. Kaltal kunci: Wireless Fidelity (Wifi), kuesioner, alkademik